Foreign products purchase intention: remarkable facts of Bangladeshi consumers - Haque, A. K. M. Ahasanul; Chowdhury, Naila Anwar; Ulfy, Mohammad Arije (Lulu Press, 2025)
The increasing cross-border trade and distribution of products has significantly expanded the availability of foreign products globally. Understanding the factors influencing consumers' intentions to purchase foreign products is crucial for survival in this competitive marketplace. This study aims to uncover these factors, with a focus on Bangladeshi consumers. Data was collected from 260 Bangladeshi consumers in Dhaka and Chittagong, the two major cities with the widest availability of foreign products. Statistical analyses were conducted using SPSS and AMOS software. Results showed that brand image and foreign product quality have significant positive effects on the purchasing intention of foreign products, while religiosity has a negative effect. The country of origin image also positively affects brand image, while ethnocentrism negatively affects foreign product quality. These findings will help marketers create effective marketing strategies and be valuable to academicians and consumers. The findings will also be valuable to marketers and academicians. The study's findings will help marketers create effective marketing strategies and benefit both academicians and consumers.